The effectiveness of school sports activities in raising the level of performance of the educational institution through purposeful educational sports media - maliani, Abdelkrim (sports creativity, 2025)
In meetings of educators, the use of the phrase “circumstances and direct social influences such as family and school” is frequently used in the context of academic success or failure, given that they do not appear in isolation from those social, economic and educational contexts that constitute the general educational environment, i.e. the educational environment in which the student lives and is affected by it socially, economically, psychologically and culturally… By examining the results of educational institutions with an analytical view and knowing the factors and researching the reasons for academic success or failure, it is possible to find appropriate methods and approaches to improve the level of these results and achieve the set goals. The social function is considered the most important function in improving school results, and this can only be achieved by activating the activities of this function, whether they are: "health, nutrition, sports, cultural, media, etc." This will reflect positively on school results and create excellence and success. However, when this function takes a superficial form that does not care about the content as much as it cares about what is put on paper, despite the material and human capabilities that the institution possesses, this will reflect negatively on its performance, reduce its productivity, and cause its students to suffer academic failure. Thus, it has not given sufficient importance to these activities and considers them secondary. Some of the prescribed school activities have not yet reached a level of attention, such as physical education, art education, and music education, as they are considered supplementary subjects and perhaps less important, despite being an integral part of the activities that take place inside and outside the educational institution, or due to the lack of communication and purposeful educational media activity that is more aware of these activities.